MUSCLE STRETCHING X DELAYED MUSCULAR PAIN: TRUTH OR MYTH? (Fiep Bulletin - online, 2014)
This research had as focus the influence of the exercises of muscle stretching to reduce delayed muscle pain (DMT) when carried through before and tests located muscle resistance (RML). The present study aimed to verify if the exercises of muscle stretching would reduce the muscle suffering noticed by students during the physical education class. The sample is compounded by a group of 46 students from schools of the Gonçalo and Itaboraí - RIO DE JANEIRO. The volunteers are separeted as follow: 28 are male and 18 are female, under the aproximated age of 16. The students performed the DML tests of going down exercises, flexion and extension, of elbows and abdomen flexion without the previous and after accomplishment of muscle stretching exercises. A after 30 hours the individuals were interviewed about the intensity of pains and noticed regions. It was uses an instrument for evaluation of these pains was composed of a human body picture under a back and front view, with one simply divided on the main regions affected beside the perception schedule subjected to Borg pain. After seven days the same volunteers performed the tests differentiating only the execution of light muscle stretching, concentrated and of short lasting before and after the tests. The procedure of the interview was repeated and then, the data comparison. As statstistics analysis, it was used the non parametric willcoxon. The test showed to be significant (p
Keywords: stretching; delayed muscle pain; Located Muscle Resistance